Relational Service Strategy and Member Participation in Savings and Loan Cooperatives: A Case Study of CU Kridha Rahardja Salatiga - Maharani, Aurora Sofia Larisa Putri; Sehabuddin, Ahmad (Universitas Tanjungpura, 2026)
Cooperatives rely heavily on active member participation for sustainability, yet many credit unions face uneven engagement despite ongoing service improvements. This study aims to describe the service strategies implemented by CU Kridha Rahardja Salatiga and analyze their role in enhancing member participation. Using a descriptive qualitative case study design, data were collected through semi-structured interviews, observations, and document analysis involving managers, staff, and members. Data were analyzed using the interactive model of Miles and Huberman. The findings show that service delivery is characterized by flexible access, responsive personal communication, simple procedures, and digital services that function mainly as supporting infrastructure. Member participation is predominantly economic, reflected in savings and loan activities, with loans acting as a key trigger of engagement. However, organizational participation, such as attendance at annual meetings, remains limited. The study highlights a Relational–Empowerment Service Model, where interpersonal relationships and economic empowerment play a more decisive role in fostering participation than digitalization alone, suggesting practical implications for semi-urban cooperatives.